UTILIZATION OF POTATO WASTE FOR PRODUCTION OF BIOETHANOL: A NOVEL TECHNOLOGY - Kumar, Dharmendra (Potato Journal, 2022)
This study was conducted on the exploration of the potential use of potato as feedstock for bioethanol production, through saccharification and fermentation. The saccharification was performed via thermal and enzymatic hydrolysis through the use of commercial enzymes such as cellulase, α-amylase, β-amylase and glucoamylosidase. The potato mash was mixed with 100 mL distilled water. The mixture was treated with different enzyme concentrations 10 U, 15 U and 20 U. The mixture was incubated at the temperature of 75 °C and pH 5.0. The saccharification process was completed with 10 U of amyloglucosidase at 60 °C, pH 4.5 for 72 h. Samples were withdrawn at different time intervals and the ethanol and consumed sugar assays were carried out by YSI Analyser. The use of commercial α-amylase led to higher reducing sugars release (69.21 ± 0.34 ± 0.32 g/100 g ) and in the combination of enzymes found the maximum efficiency of saccharification i.e. 81.40 ± 0.56 g/100 g. The results showed that the enzymatic treatment led to higher saccharification efficiency (81.40%) equivalent to 96% of the maximum theoretical. The fermentation process by using various strains of Yeast at different time intervals. The maximum ethanol yield was obtained by Saccharomyces cerevisiae MTCC 178 after 72 h was 84.19 g/L.